Effects of diets, foods and nutrients on immunity: Implications for COVID‐19?. Issue 4 (11th December 2020) - Lockyer, S.
Abstract: The COVID‐19 pandemic has sparked an increase in claims that particular food and drink products and nutritional supplements are able to 'boost' immunity. The immune system is highly complex, consisting of many different cell types and processes, and nutritional adequacy is undoubtedly required to support its function. Specific roles have been established for several micronutrients including vitamins A, B6, B12, C and D, copper, folate, iron, selenium and zinc, with documented impacts on particular aspects of immune function as a result of clinical deficiencies. Increased susceptibility to infections and poorer outcomes have been commonly observed in cases of undernutrition. However, high bodyweight, diabetes and ageing are also associated with immune dysfunction. The gut microbiota is intimately linked with the immune system and there is some evidence to suggest that food components that favourably modify its composition, such as pre‐ and probiotics, may be advantageous in immune modulation. Studies also indicate some benefits of specific supplements; for example, zinc and vitamin C supplements have been shown to reduce the duration of the common cold; probiotics have been suggested to reduce the duration and severity of acute infectious diarrhoea and prevent antibiotic‐associated diarrhoea; and anti‐inflammatory effects of long‐chain omega‐3 fatty acids have also been demonstrated. However, at present there are no authorised EU health claims for any of these effects. In the light of the recent media interest in the role of diet and lifestyle on the immune system following the COVID‐19 outbreak, this article will summarise why a healthy, balanced diet is key to supporting immune function with consideration given to the latest thinking in relation to COVID‐19.